Geospatial Mapping of Crop Types and Land Cover in the MFS Action Sites in Bangladesh: Crop Area Mapping - Gupta, Sweta; Mathieu, Renaud Serge Alexis; Bhandari, Humnath (International Rice Research Institute, 2023)
Mixed farming is defined as agricultural production systems with the integration of crops, agroforestry, fisheries, and livestock in a system approach. Crops and livestock are critical components of the mixed farming system. The sustainable intensification of the mixed farming systems entails the integration of different components of the mixed farming systems with efficient and sustainable use of resources, such as the use of domesticated animal manure (organic farming) for crop production, feeding crop residues to livestock, growing crops with fruit trees, integrating fish with rice (rice-fish farming), and so on. It provides a high return on agricultural labor because every product is utilized.